Testosterone-induced micronuclei and increased nuclear division rate in L929 cell line expressing the androgen receptor. Issue 5 (August 2015) - Stojkovic, Ranko; Ivankovic, Sinisa; Ivankovic, Dusica; Attias, Leonello; Mantovani, Alberto; Fucic, Aleksandra
Highlights Testosterone significantly increases MN frequencies in L929 cells. Nuclear division index is higher after 48 h than 24 h of incubation with testosterone. A benchmark doses for MN and nuclear division index differ.